Utilization of Styrofoam Waste as an Additive in AC-BC Mixture with Variations in Compaction Temperature - Theovani, Gabriel Julio; Azwansyah, Heri; Mayuni, Siti (Fakultas Teknik Universitas Tanjungpura, 2025)
Styrofoam, a polystyrene-based plastic widely used in packaging, poses serious environmental challenges due to its non-biodegradable nature. Its use as an additive in asphalt mixtures provides dual benefits: reducing plastic waste and improving pavement performance. This study evaluates the effects of styrofoam addition and variations in compaction temperature on the Marshall characteristics of Asphalt Concrete